Characterization of InAs / GaAs QD structures by HREM and PL spectroscopy - Atıcı, Y.; Cherns, D.; Polımenı, A.; Henını, M.; Eaves, L. (My University, 1999)
-
Keywords: Nanobilim ve Nanoteknoloji; Fizik; Katı Hal